Using Gamification Through Proprofs in Learning: A Systematic Literature Review - Wahyuni Arafani (Indonesian Publication Center, 2025)
This study aims to analyze the role of gamification adaptation using the ProProfs platform in science learning, especially on human digestive system material. The research method used is Systematic Literature Review (SLR), which involves evaluating 10 relevant articles from 2020-2024. The results showed that gamification through ProProfs increased students' motivation, engagement and self-learning. Game elements such as points, levels and leaderboards encourage active participation and provide an interactive and fun learning experience. ProProfs also facilitates effective evaluation with immediate feedback, while honing students' social skills and digital literacy. In conclusion, the use of ProProfs in science learning has a significant positive impact on student learning outcomes, and can be further integrated in the curriculum with teacher training and ongoing evaluation